Evaluation the resistance of cocoa clones (Theobroma cacaoL.) - Agung Wahyu Susilo; Indah Anita Sari (Indonesian Coffee and Cocoa Research Institute, 2014)
Acceleration on clonal selection of cocoa resistance to pod rot (Phytophthora palmivora)was carried out by early evaluation of the resistance using laboratory test. This research has objective to select the promising clone resistance to P. palmivora for field evaluation. Trials were carried out at the Laboratory of Plant Pathology at the Indonesian Coffee and Cocoa Research Institute using in-vitro inoculation. Isolate of P. palmivorawere collected from the infected pods at Jatirono Estate, Banyuwangi then inoculated to three mature pods of each tested clones. Trials were carried out in two steps to confirm the stability of performance of the resistance. A total of 41 clones were tested in these trials. However due to the availability of pod sample was limited then at 1st trial 31 clones were tested and at 2nd trial 37 clones were tested, both of the test using 27 same clones. The assessed variables were lesion size on pod surface due to Phytophthorainfection at 1st to 7th day after inoculation. The lesion sizes were significantly different among tested clones that performing any variability of the resistance. The variability were grouped into five groups as the resistant classification by which three clones were identified, namely Jano/IV/4/13 (TSH 858 x ICS 13), Jano next to I/7 and Kate/I/10/18 (Sulawesi 01 x TSH 858) consistently performing lowest size of the lesion compared to Sca 6 that could be selected as the resistant clones for field evaluation. Key words: cocoa clones, resistance, pod inoculation, Phytophthora palmivora